The Role of HEART Score in Predicting Major Adverse Cardiac Events in Patients with Possible Acute Coronary Syndrome Presenting to the Emergency Department - Afroz, Fahdia; Ullah, Mohammad; Nabi, Shah Golam; Tuhin, Md Ruhul Amin; Rahman, Md Mahbubur; Abdullah, Md; Islam, Md Saiful; Arefin, Md Minhaj (Cardiovascular Journal, 2023)
Introduction: Acute coronary syndrome is very challenging & sometimes very confusing to diagnose. The HEART score was designed to be a prognostic prediction model, using information from the patient’s history, ECG, age, risk factors, and troponin level at the initial emergency department. This study was conducted to assess the role of HEART score in predicting major adverse cardiac events in patients with possible acute coronary syndrome presenting to the emergency department. Methods: This prospective observational study was conducted among 453 patients presented with acute coronary syndrome (ACS) at the Department of Cardiology, National Institute of Cardiovascular Diseases, Dhaka, Bangladesh from January 2023 to June 2023 to assess the role of HEART score in predicting major adverse cardiac events (MACE) in patients with possible acute coronary syndrome. The study population was divided into two groups depending on HEART score. MACE was observed between these two groups. Results: Mean age of the respondents was 53.45±11.23 years where 77.7% of them were male. 55% had smoking habit, 36% had history of Diabetes Mellitus, and 38% had history of HTN. Among the respondents 62.9 % was improved. 11.03 % respondents developed heart failure, 14.34% recurrent ischemic pain, 7.9% of recurrent MI, 2.8 % cardiogenic shock, and 0.88 % cases of death. HEART score as predictor was statistically significant (X2=69.7, df=1, p<0.05), indicated to distinguish between major adverse cardiac events and no major cardiac events. Conclusion: Almost one third of respondents with high HEART score had heart failure and recurrent ischemic pain. There was statistically significant difference in incidence of major adverse cardiac events between high and low HEART score groups. The HEART score can be used to predict risk for major adverse cardiac events effectively in patients with suspected ACS. This can help us to determine needs for urgent treatment and hospitalization among the patients who present with suspected ACS. Cardiovasc j 2023; 16(1): 9-16